Influence of micro-patterning of the growth template on defect reduction and optical properties of non-polar (112ˉ0) GaN. (20th October 2020) - Bruckbauer, Jochen; Gong, Yipin; Jiu, Ling; Wallace, Michael J; Ipsen, Anja; Bauer, Sebastian; Müller, Raphael; Bai, Jie; Thonke, Klaus; Wang, Tao; Trager-Cowan, Carol; Martin, Robert W
Abstract: We investigate the influence of different types of template micro-patterning on defect reduction and optical properties of non-polar GaN using detailed luminescence studies. Non-polar ( 11 2 ˉ 0 ) (or a -plane) GaN exhibits a range of different extended defects compared with its more commonly used c -plane counterpart. In order to reduce the number of defects and investigate their impact on luminescence uniformity, non-polar GaN was overgrown on four different GaN microstructures. The micro-patterned structures consist of a regular microrod array; a microrod array where the − c -side of the microrods has been etched to suppress defect generation; etched periodic stripes and finally a subsequent combination of etched stripes and etched microrods (double overgrowth). Overall the presence of extended defects, namely threading dislocations and stacking faults (SFs) is greatly reduced for the two samples containing stripes compared with the two microrod samples. This is evidenced by more uniform emission and reduction in dark regions of non-radiative recombination in room temperature cathodoluminescence imaging as well as a reduction of the SF emission line in low temperature photoluminescence. The observed energy shifts of the GaN near band edge emission are related to anisotropic strain relaxation occurring during the overgrowth on these microstructures. A combination of stripes and microrods is a promising approach for defect reduction and emission uniformity in non-polar GaN for applications in light-emitting devices as well as power electronics.